In oceans deep : courage, innovation, and adventure beneath the waves - Streever, Bill (Little, Brown and Company, 2019)
In an age of unprecedented exploration and innovation, our oceans remain largely unknown, and endlessly fascinating: full of mystery, danger, beauty, and inspiration. Bill Streever-a longtime deep-sea diver himself-has masterfully woven together the science and history of Earth's last remaining frontier: the sea. In Oceans Deep celebrates the daring pioneers who tested the limits of what the human body can endure under water: . free divers able to reach 300 feet on a single breath; engineers and scientists who uncovered the secrets of decompression; teenagers who built their own diving gear from discarded boilers and garden hoses in the 1930s; saturation divers who lived under water for weeks at a time in the 1960s; and the trailblazing men who voluntarily breathed experimental gases at pressures sufficient to trigger insanity. Tracing both the little-known history and exciting future of how we travel and study the depths, Streever's captivating journey includes seventeenth-century leather-hulled submarines, their nuclear-powered descendants, a workshop where luxury submersibles are built for billionaire clients, and robots capable of roving unsupervised between continents, revolutionizing access to the ocean.